Tindak Pidana Pencucian Uang (Money Laundering) dan Strategi Pemberantasan - Ayumiati Ayumiati (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2012)
Money laundering is a criminal offense had been committed in order to disguise the origin of the wealth that was haram to be halal. Thus the launderer can develop, especially the illegal business of narcotics crimes. Crimes related to narcotics money laundering because of drug crimes are crimes of origin (predicate crime), and advanced money laundering is a crime (crime derivative). The birth of anti-money laundering regime is internationally starts with the issuance United Nations Conventions Against Illicit Traffic in Narcotic Drugs and Psychotropic Substances in 1988 which is the culmination of the crime of money laundering combating illicit narcotics and psychotropic substances. In 2002 and 2003 the government of Indonesia passed legislation that is anti-money laundering Law No. 15 Year 2002 jo. Act No. 23 of 2003 in which a drug crime as evil places of origin of money laundering.